Beyond heuristics: CFD‐based novel multiparameter scale‐up for geometrically disparate bioreactors demonstrated at industrial 2kL–10kL scales. Issue 6 (6th April 2020) - Scully, James; Considine, Laura B.; Smith, Mark T.; McAlea, Eamonn; Jones, Nephi; O'Connell, Edel; Madsen, Emilee; Power, Martin; Mellors, Philip; Crowley, John; O'Leary, Niall; Carver, Scott; et al.
Abstract: The timely delivery of the most up‐to‐date medicines and drug products is essential for patients throughout the world. Successful scaling of the bioreactors used within the biopharmaceutical industry plays a large part in the quality and time to market of these products. Scale and topology differences between vessels add a large degree of complication and uncertainty within the scaling process. Currently, this approach is primarily achieved through extensive experimentation and facile empirical correlations, which can be costly and time consuming while providing limited information. The work undertaken in the current study demonstrates a more robust and complete approach using computational fluid dynamics (CFD) to provide potent multiparameter scalability, which only requires geometric and material properties before a comprehensive and detailed solution can be generated. The CFD model output parameters that can be applied in the scale‐up include mass transfer rates, mixing times, shear rates, gas hold‐up values, and bubble residence times. The authors examined three bioreactors with variable geometries and were able to validate them based on single‐phase and multiphase experiments. Furthermore, leveraging the resulting CFD output information enabled the authors to successfully scale‐up from a known 2kL to a novel and disparate 5kL single‐use bioreactor in the first attempted cell culture. This multiparameter scaling approach promises to ultimately lead to a reduction in the time to market providing patients with earlier access to the most groundbreaking medicines. Abstract : In this study, the authors used CFD methods to successfully scale up from a known 2kL bioreactor to a novel and disparate 5kL single‐use bioreactor in the first attempted cell culture. This approach leveraged numerous scaling parameters including mass transfer rates, mixing times, shear rates, gas holdup values and bubble residence times and promises to ultimately lead to a reduction in the time to market providing patients with earlier access to the most groundbreaking medicines.